越南学生汉语习得中的韵母偏误分析 - Khưu Chí Minh; Cái Thi Thủy; Nguyen Thi Thanh Huong; Huỳnh Bích Ngọc (Universitas Tanjungpura, 2023)
本文对汉语和越南语韵母系统进行了较详细的描写，同时对标准越南语与越南三大方言的韵母系统进行对比，以便找出越南学生在汉语习得过程中所存在的区域性韵母偏误。通过汉越韵母系统的对比本文指出二者在构成情况、韵母数量、拼写方式、语音等方面的异同。越南学生区域性语音偏误规律的分析结果表明不同区域的越南学生有不同的韵母偏误。本文运用理论对这些偏误进行解释，从而探讨偏误的成因,以求找出克服的方案以及提出教学建议。希望本研究结果能给从事汉语语音教学的工作者提供参考，使教学工作更加有针对性，从而能够提高教学效率，同时也希望对汉语学习者有所帮助。 This article describes the vowel of Chinese and Vietnamese, and compares the vowel of standard Vietnamese and the three major Vietnamese dialects in order to find out the regional vowel errors that Vietnamese students have in the process of Chinese acquisition. Through the comparison of Chinese and Vietnamese vowel systems, the article points out similarities and differences in phonetic aspects, writing methods, number of patterns, and composition of Vietnamese and Chinese. According to the analysis results of the regional wrong phonetic rule of Vietnamese students, Vietnamese students in different regions will have different vowel errors. The article has applied theory to explain these errors, thereby finding the causes of errors, finding solutions to overcome and making recommendations on teaching. It is hoped that the results of this research can be a reference for those who do the teaching of Chinese phonetics, making the teaching on target, thereby improving the teaching efficiency, improving the teaching efficiency, and at the same time also hope it helps the learners.